The Oblique Impact On Crash Barrier - Foong, Yoo Kim (UTeM, 2008)
Guardrail is typically designed to guide and restrain errant vehicles, ranging from small cars to heavy goods vehicles. The main objective of this thesis is to investigate the impact energy absorption of a guardrail due to impact with a vehicle in the various angles. The various angles of oblique loading are test with 20°, 45°,75° and 90°. The model of the guardrail will be built with Solidworks 2007 and the finite element model will be used to simulate the impact of guardrail with ABAQUS software. The ABAQUS software will produce some important output data for this research such as reaction force, type of energy and deformation. These data will be used to gain the energy absorb after the impact to the guardrail. The energy absorb can be obtained from two methods. Deduction between the total energy and kinetic energy will be the first method to obtain the energy absorb. The next method is the result of area under curve for reaction force versus deformation graph and the NCSS software will be used to obtain the result.